2011
DOI: 10.1007/978-3-642-20267-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Online Adaptation of Path Formation in UAV Search-and-Identify Missions

Abstract: Abstract. In this paper, we propose a technique for optimisation and online adaptation of search paths of unmanned aerial vehicles (UAVs) in search-and-identify missions. In these missions, a UAV has the objective to search for targets and to identify those. We extend earlier work that was restricted to offline generation of search paths by enabling the UAVs to adapt the search path online (i.e., at runtime). We let the UAV start with a pre-planned search path, generated by a Particle Swarm Optimiser, and adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…They showed that the two GAs are much faster than a local hill climbing algorithm and a complete-coverage algorithm. van Willigen et al [18] proposed a particle swarm optimization (PSO) algorithm to generate a pre-planned UAV path for missions that involve searching and identifying targets. The path can be adapted at runtime based on the information acquired during the remainder of the mission.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that the two GAs are much faster than a local hill climbing algorithm and a complete-coverage algorithm. van Willigen et al [18] proposed a particle swarm optimization (PSO) algorithm to generate a pre-planned UAV path for missions that involve searching and identifying targets. The path can be adapted at runtime based on the information acquired during the remainder of the mission.…”
Section: Related Workmentioning
confidence: 99%
“…Na literatura, foram encontradas várias referências sobre aplicações de Veículos Aéreos Não Tripulados para realizar diferentes tarefas. A maioria das aplicações encontradas Jacques (2002), Cooper e Goodrich (2008), Pitre, Li e DelBalzo (2009), George, Sujit e Sousa (2011), Willigen et al (2011) se concentram em tarefas relacionadas à missões militares como busca, detecção, reconhecimento, rastreamento e ataque a alvos móveis e realocáveis, e utilizam sensores como câmeras fotográ cas, de vídeo e de infravermelho, sensores de temperatura, ultravioleta, laser e detectores de reagentes químicos. Entretanto, como pode ser observado na classi cação da UVS International, graças ao avanço tecnológico nos setores de processamento de dados e a miniaturização de componentes eletrônicos ocorridos nas últimas duas décadas, • Aquisição de dados e imagens de alvos em áreas inacessíveis por meios terrestres;…”
Section: Aplicações Dos Vantsunclassified